2021
DOI: 10.1111/cid.13032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the accuracy of implant placement using different drilling systems for static computer‐assisted implant surgery: A simulation‐based experimental study

Abstract: Background Different designs of surgical drilling systems have been developed for the purpose of static Computer‐Assisted Implant Surgery (sCAIS), but there is at present little understanding of how design principles affect the accuracy of implant placement. Purpose The aim of this in vitro study was to compare the accuracy of implant placement among five drilling systems of sCAIS in a controlled experimental setting. Materials and Methods Twenty‐five 3D printed models with two edentulous bilateral premolar sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 25 publications
2
36
0
1
Order By: Relevance
“…Therefore, these findings should be taken into consideration when immediate or early implant placement using sCAIS is planned after tooth extraction. The findings observed in this study agree with previous studies evaluating different implant systems, where differences in implant positional accuracy were found between and within manufacturers [ 17 , 18 ]. The differences between systems could be explained by drilling system design and protocol since the implant macro-design is similar between both investigated implants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, these findings should be taken into consideration when immediate or early implant placement using sCAIS is planned after tooth extraction. The findings observed in this study agree with previous studies evaluating different implant systems, where differences in implant positional accuracy were found between and within manufacturers [ 17 , 18 ]. The differences between systems could be explained by drilling system design and protocol since the implant macro-design is similar between both investigated implants.…”
Section: Discussionsupporting
confidence: 92%
“…These differences may be related to the macro-design of the implants, and the variations in design or tolerances of components, such as surgical drills, drill keys, and guide-hole sleeves used for guided implant site osteotomy and placement. To enhance the accuracy of sCAIS, alternative implant systems or surgical guide design options focusing on the reduction of components, such as keyless compared to drill-key systems or sleeveless (SL) versus manufacturer’s sleeve [ 19 ] guide-hole designs have been introduced to the market [ 18 ]. Interestingly, recent studies have reported higher accuracy of final 3D implant position when SL guide-hole designs were used [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several designs of drilling systems are available for s-CAIS, including sleeve-in-sleeve system, sleeve-in-sleeve with self-locking, the mounted sleeve-on-drill, the integrated sleeve-on-drill, and the integrated sleeve-on-drill without a metal sleeve. The sleeve-in-sleeve system, used in the present study, was shown to lead to significantly less angular deviation compared to other systems listed above [ 40 ]. Regarding the IOS, the accuracy of IOS for single implant was widely demonstrated [ 41 , 42 ] and should, therefore, be considered as a valid research tool complying with (ALADA) principles for patient radiation safety [ 43 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these simple mounting devices are rarely used in published studies. Clinically, instead of stoppers, the use of spacers resembling implant key heights (El Kholy et al, 2019;Sittikornpaiboon et al, 2021) eliminate errors of adjustment, reading and movement of stoppers, and spare clinicians the continuous monitoring of the position of stoppers. Recommendations:…”
Section: Stoppers and Spacersmentioning
confidence: 99%